Does Diversification Strengthen Or Weaken A Firm’s Performance On Stock Price? - Sari, Elvi Sekar; Tjaraka, Heru (Dinasti Publisher, 2025)
This study examines the impact of diversification on a firm’s performance, specifically in relation to its stock price. The primary aim is to assess whether diversification strengthens or weakens the effect of financial performance on stock prices.The research uses Price-to-Book Value (PBV) as a measure of stock price and Return on Assets (ROA) as a measure of financial performance. The sample consists of 292 companies, with data analyzed through descriptive statistics, regression analysis, and ANOVA. The findings suggest that financial performance, as measured by ROA, has a significant positive effect on PBV, indicating that better financial performance tends to enhance a company's stock price. However, the study also explored whether diversification both international and industrial moderates this relationship. The results showed that while diversification strategies were prevalent in the sample, they did not significantly weaken or strengthen the relationship between ROA and PBV. These findings imply that while financial performance plays a crucial role in determining stock prices, diversification, in this context, does not have a notable moderating effect. This study contributes to the ongoing debate regarding the impact of diversification on firm performance, suggesting that, although diversification may reduce risk, it does not necessarily amplify the financial performance’s impact on stock prices. Further research could explore other factors influencing this relationship and test these findings across different industries and time periods.